2014
DOI: 10.1111/1756-185x.12306
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated risk factors for work disability in Egyptian patients with ankylosing spondylitis from one center

Abstract: The prevalence of WD among Egyptian patients with AS is considerably high. Clinical and psychosocial factors, in particular, appear to be associated with WD and should therefore be prioritized in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The initial search yielded 1391 citations, from which 21 studies were identified for inclusion after screening [6,35,46,[49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66] (Fig. 1).…”
Section: Study Selection Characteristics and Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial search yielded 1391 citations, from which 21 studies were identified for inclusion after screening [6,35,46,[49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66] (Fig. 1).…”
Section: Study Selection Characteristics and Quality Assessmentmentioning
confidence: 99%
“…The majority (six of nine) of studies that evaluated economic burden of delayed diagnosis assessed work disability or employment; in all of these studies, longer diagnosis delay was associated with a greater likelihood of work disability or unemployment [46,52,56,58,62,66] (Table 4). In the three studies that evaluated treatment costs and healthcare utilization, longer diagnosis delay was associated with higher costs related to doctors' visits and specialist services [35,57], unnecessary spinal surgery [35], and treatments [57,66] (Table 4).…”
Section: Economic Burden Of Delayed Diagnosismentioning
confidence: 99%
“…The bulk of studies showed that the prevalence of work disability is high in these patients and is associated with both clinical and psychosocial factors. 13,14 Specifically, labour-intensive jobs and manual professions were associated with poorer work outcomes. 13,15 Ulus et al compared ankylosing spondylitis patients with healthy controls and found that functional impairment assessed by BASFI was a significant predictor of work instability scores.…”
Section: Discussionmentioning
confidence: 99%
“… 74 Work disability was greater in SpA patients with delayed diagnosis when compared with early diagnosis. 70 , 72 , 83 , 98 , 99 In a retrospective study on Health Search Database in Italy, 1084 patients were identified with a delay in diagnosis of three years. During this delay, approximately €153,000 were spent on services related to specialist visits and drugs not related to SpA.…”
Section: Discussionmentioning
confidence: 99%
“…Different factors were associated with disability, including delayed diagnosis, lower educational level, manual work, rural living, peripheral arthritis manifestation, and psychological factors. 99 To date, there are no published studies from Saudi Arabia that assessed the HRCU costs of SpA and the impact of the delayed diagnosis on costs.…”
Section: Discussionmentioning
confidence: 99%